Modern Information Technologies and the Need for Improving the Quality of Organizational and Corporate Structures' Management - Shestakov, Aleksandr L.; Loginovskiy, Oleg V.; Maksimov, Alexander A.; Hollay, Aleksandr V. (2020 Global Smart Industry Conference (GloSIC), 2020)
This paper provides a review of modern information technologies used in management of industrial enterprises and corporations, as well as of government authorities. Despite the success achieved in the field of the speed of operation of computers and supercomputers, and of various analyzing systems, the implementation of modern information technologies does not ensure the improvement of the quality of managing different organizational and corporate structures. The many-years' experience in engineering and operation of various automated, information-computing, analytical, expert, and other systems has shown that the implementation of these systems was not always beneficial in terms of improving the organizational management quality, or making the activity of the structures, where these systems had been introduced, more efficient. In this context, today, it is of utmost importance to understand that the reasons for such slightly disappointing results of implementing various information systems do not lie in the technical capacities of the computing machines, but can rather be explained by the fact that the methods, models and technologies of management at all the stages of elaboration and making of decisions have remained essentially the same as in the last quarter of the past century. The lagging behind in the development of the methods and algorithms has lead to a situation when the capacities of the computing machines are not used to their maximum. Thus, an important task of the management theory and practice is to close the gap between the methods of decision making and the modern level of the computing equipment. The paper sets forth a task on making sure that the development of the computing machines is harmonized with the processes of improving and implementing the managerial algorithms. The causes of the abovementioned lagging behind are described, and the recommendations are given on how to eliminate the existing gap.